Automatizacion de la subestacion electrica jesus de 138kv – arequipa a traves del protocolo de comunicacion iec 61850 - Rojas Llerena, Alan Santiago (2018)
The objective of this work is to develop the process about automation of an electrical substation using the IEC 61850 communication standard, as well as modern tools and communication equipment for an effective and reliable integration of the different devices into the system. The question is: how to automate an electrical substation? The answer is technology, now thanks to the evolution on the integrated systems (relays based on microprocessors) as well as the digitized systems and data networks, the control systems of the substations have achieved substantial improvements with respect to traditional equipment. To automate an electrical substation, a series of steps must be followed. First, the development and engineering of the communication architecture, define equipment, specify the way how they will be connected and the type of cable to be used. Once all the relays (protection and measurement equipment) are connected, they must be integrated into the data concentrator, being through the IEC 61850 communication standard. Once the integration is completed, a SCADA - HMI system is developed, which serves for supervision and remote control of the entire electrical system. And finally the report is configured, which is the main task of the automation, sending all the reports of the signals of the protection and measurement equipment to the Scada system of the Control Center. The results obtained were satisfactory fulfilling all the proposed objectives. The Jesús electrical substation located in the city of Arequipa is in operation after performing the tests of each of the signals to be reported with the Control Center - SEAL.